HFIP-Induced Allylation Reaction of Tertiary Allylic Alcohols with Thiols or Sulfonyl Hydrazines to Access Allylic Organosulfurs - Lu, Maojian; Zhang, Rong-Jin; Zhu, Can-Ming; Xiao, Yonghong; Chen, Jian-Rui; Zhao, Lei-Min; Tong, Qing-Xiao; Zhong, Jian-Ji (Synlett, 2022)
A simple and transition-metal-free HFIP-induced allylation reaction of tertiary allylic alcohols with thiols or sulfonyl hydrazine derivatives was reported for the efficient and highly selective synthesis of allylic sulfides and allylic sulfones. Herein, HFIP played a vital role in not only activating the allylic alcohol, but also stabilizing the allylic cation intermediate to accelerate the subsequent transformations.
Keywords: organosulfurs; HFIP; allylation; allylic alcohol